1999
DOI: 10.1080/135765099397015
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic and Phonological Facilitation from Unattended Words: Evidence for Bilateral Processing

Abstract: This study investigated hemisphere differences in sensitivity to orthographic and phonological similarity using a task that did not require deliberate metalinguistic comparisons between words. Two experiments investigated the influence of an unattended distractor item on the pronunciation of target words in the right visual field (RVF) and left visual field (LVF) in neurologically intact persons. W ord and pseudoword distractors that were both orthographically and phonologically similar to the target word prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The hemispheric distribution of the effects, with recordings over the left hemisphere sensitive to both phonological priming and orthographic congruence and those over the right hemisphere sensitive only to phonological priming, is difficult to interpret given the poor spatial resolution of the ERP method: It should not be assumed that left‐lateralized effects have left hemisphere generators. That being said, behavioral studies using the divided visual field technique have reported both orthographic and phonological facilitation in pronouncing target words for both right and left visual field presentations of priming words (e.g., Chiarello & Hasbrooke, ), consistent with roles for both hemispheres in single‐word language processing. Others have similarly reported that single‐word phonological and orthographic codes are represented in both hemispheres in spoken word processing, but that integration occurs primarily in the left hemisphere (e.g., Zecker, Tanenhaus, Alderman, & Siqueland, ), consistent with our finding of less priming for nonmatching targets over left hemisphere sites.…”
Section: Discussionmentioning
confidence: 80%
“…The hemispheric distribution of the effects, with recordings over the left hemisphere sensitive to both phonological priming and orthographic congruence and those over the right hemisphere sensitive only to phonological priming, is difficult to interpret given the poor spatial resolution of the ERP method: It should not be assumed that left‐lateralized effects have left hemisphere generators. That being said, behavioral studies using the divided visual field technique have reported both orthographic and phonological facilitation in pronouncing target words for both right and left visual field presentations of priming words (e.g., Chiarello & Hasbrooke, ), consistent with roles for both hemispheres in single‐word language processing. Others have similarly reported that single‐word phonological and orthographic codes are represented in both hemispheres in spoken word processing, but that integration occurs primarily in the left hemisphere (e.g., Zecker, Tanenhaus, Alderman, & Siqueland, ), consistent with our finding of less priming for nonmatching targets over left hemisphere sites.…”
Section: Discussionmentioning
confidence: 80%
“…The further left on the handedness continuum, the more reading errors are made (Annett, 1991;Tremblay, Monetta, & Joanette, 2004). Moreover, it has been established that while the right hemisphere may have a role in phonological processing of print, the left hemisphere is far more suited for this task when phonological processing complexities increase (Chiarello, Hasbrooke, & Maxfield, 1999).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%